Antigen-Specific Immunoadsorption With the Glycosorb® ABO Immunoadsorption System as a Novel Treatment Modality in Pure Red Cell Aplasia Following Major and Bidirectional ABO-Incompatible Allogeneic Hematopoietic Stem Cell Transplantation - Handisurya, Ammon; Worel, Nina; Rabitsch, Werner; Bojic, Marija; Pajenda, Sahra; Reindl-Schwaighofer, Roman; Winnicki, Wolfgang; Vychytil, Andreas; Knaus, Hanna A.; Oberbauer, Rainer; Derfler, Kurt; Wohlfarth, Philipp (Frontiers in Medicine, 2020)
Pure red cell aplasia (PRCA) after ABO-incompatible allogeneic hematopoietic stem cell transplantation (HSCT) is caused by persisting host-derived isohemagglutinins directed against donor red blood cell (RBC) antigens. ABO antigen-specific immunoadsorption (ABO-IA) with Glycosorb, commonly used for desensitization therapy in ABO-incompatible living donor renal transplantation, specifically eliminates circulating isohemagglutinins and might represent a novel treatment option for post-HSCT PRCA. In this prospective observational (n=3) and retrospective (n=3) analysis of six adult HSCT-recipients with PRCA, ABO-IA was initiated at 159 (range: 104-186) days following HSCT. The median treatment frequency was 4.5 (range: 3.9-5.5) sessions/week. ABO-IA-treatment led to a continuous decrease in isohemagglutinin titers. Reticulocytes increased to ≥30 G/L after 17.5 (range: 4-37) immunoadsorption sessions over 28.5 (range: 6-49) days and continued to rise thereafter. By the end of the three-month follow-up period after discontinuation of ABO-IA, all patients showed a sustained remission of PRCA and were independent from erythropoietin-stimulating agents and transfusions. No case of infection or GVHD was observed. After a median follow-up of 22.03 (range: 6.08-149.00) months after ABO-IA-treatment, all patients were alive and showed a stable RBC engraftment of the donor blood group. Our data provide the first evidence for ABO-IA as an effective treatment for post-HSCT PRCA.